Reflective Thinking Assessment Among Doctor of Physical Therapist(DPT) Students at Riphah International University - Saba Rafique, Maryam Shabbir, Hafiza Mehjabeen, Sumera Azam, Sans Arif, Nishat Riaz, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Reflection is the Latin origins means to turn back or to bend. Reflection in the educational context can be considered as a process in which thoughts are ‘turned back’ so that they can be interpreted or analyzed. The trigger to this sense-making process is usually an event or situation and the outcome of the process is increased understanding or awareness. Objectives: The objective of this study is to assess the reflective thinking among doctor of physical therapy students (DPT) at Riphah international university. Methodology: This observational cross-sectional study was done at Riphah international university Lahore and was compiled at RCRS Lahore. Study was completed in 6 months after approval of synopsis. Non probability, convenience sampling was used. Sample size was calculated to be 120.The response rate was 95%. Questionnaire for reflective thinking was used to find out the level of thinking in DPT students. Results: There was significant difference within each semester and between first to eight semesters. But differences were not increases or decreases gradually. According to data collected from different students at Riphah international university the value of habitual behavior is 0.00 which is significant, value of understanding value is also 0.00, value of reflection is 0.005 and value of critical reflection is also significant 0.000. Conclusion: Current study found that reflective thinking can be develop by individuals but guided reflection with a supervisor or mentor is important so that it will gradually increases from 1st to 8th semester.